2010
DOI: 10.1111/j.1365-2141.2010.08161.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of post‐transplant lymphoproliferative disorder in solid organ transplant recipients – BCSH and BTS Guidelines

Abstract: SummaryA joint working group established by the Haemato-oncology subgroup of the British Committee for Standards in Haematology (BCSH) and the British Transplantation Society (BTS) has reviewed the available literature and made recommendations for the diagnosis and management of post-transplant lymphoproliferative disorder (PTLD) in adult recipients of solid organ transplants. This review details the risk factors predisposing to development, initial features and diagnosis. It is important that the risk of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
173
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 123 publications
3
173
3
3
Order By: Relevance
“…27,29 The PTLD, which is the most important EBVassociated disorder, can be prevented by modulation of the immune system, autologous expanded T-cell infusion, and/or use of anti-EBV drugs such as rituximab. 12,30 The incidence of PTLD in liver recipients in this study was 4.9% (34 of 696 patients); this is in agreement with other studies (1.6%-15%). In another study conducted in our center from 2003 to 2010, the incidence of PTLD was 0.9% (5 patients with PTLD in 550 liver transplant 31 This difference may be explained by the use of more potent immunosuppressive regimens in the later years and higher index of suspicion of our clinicians to diagnose PTLD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…27,29 The PTLD, which is the most important EBVassociated disorder, can be prevented by modulation of the immune system, autologous expanded T-cell infusion, and/or use of anti-EBV drugs such as rituximab. 12,30 The incidence of PTLD in liver recipients in this study was 4.9% (34 of 696 patients); this is in agreement with other studies (1.6%-15%). In another study conducted in our center from 2003 to 2010, the incidence of PTLD was 0.9% (5 patients with PTLD in 550 liver transplant 31 This difference may be explained by the use of more potent immunosuppressive regimens in the later years and higher index of suspicion of our clinicians to diagnose PTLD.…”
Section: Discussionsupporting
confidence: 82%
“…19,34 Although it is difficult to subcategorize PTLD lesions, 30,37 the most common PTLD lesion in our patients was monomorphic (5 of 34 patients), which is similar to data from other studies including a previous study in our center (3 of 5 patients). 30,31,37 A previous study reported that the monomorphic type occurred in 31%, polymorphic type in 19%, and hyperplastic form of early lesions in 1% patients. 38 Because the highest PTLD incidence and mortality were seen in pediatric liver transplant recipients, timely diagnosis of this complication before appearance of clinical symptoms is important.…”
Section: Discussionmentioning
confidence: 99%
“…Both infectious diseases and malignancies represent two groups of common complications in the post-transplant period. These complications are often characterized by poorly specific clinical symptoms particularly in early stages [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the gastrointestinal system is the most frequently affected site in renal transplant patients. 1 Posttransplant lymphoproliferative disorders are more common in solid-organ transplant recipients than in hematologic stem cell recipients, and many of the cases of intestinal PTLDs reported are of B-cell phenotype. 4 On the other hand, T-cell PTLDs emerge primarily at extranodal sites, including bone marrow and spleen, and the small bowel is an infrequent location.…”
Section: Discussionmentioning
confidence: 99%
“…1 Posttransplant lymp hoproliferative disorders of T-cell origin are rarer and less frequently associated with EBV. 2 A T-cell PTLD may occur as any T-cell lymphoma listed in World Health Organization classification, but anaplastic large-cell lymphoma is the most frequent.…”
Section: Discussionmentioning
confidence: 99%